(untitled) (Agronomy Journal of Nepal, 2022)
A field experiment was conducted during the winter season at Tamsariya-7, Nawalparasi, Nepal to determine the effect of sowing dates on growth and yield of rapeseed varieties. Four varieties of rapeseed (Unnati, Preeti, Pragati and Local) were planted in four sowing dates; October 13th, October 28th, November 12th and November 27th. The experiment was laid out in split-plot design with sowing date in the main plot and varieties in the sub-plot. Significant variations due to sowing dates and varieties were observed in plant height, leaf area index, dry matter accumulation, branches per plant, number of siliqua per plant, siliqua length, number of seeds per siliqua, abortion percentage, test weight and the grain yield. Results showed that the highest grain yield (1.278 t/ha) was obtained from the October 28th sowing date and it was statistically different from the yield of all other dates of sowing. There were 17.05%, 40% and 62.18% reduction in grain yield for October 13th, November 12th and November 27th sowing dates compared to October 28th sowing date. Variety Preeti was the highest yielding variety for October sowing while variety Unnati was the highest yielding variety for November sowing. So, variety Preeti sown on October 28th is recommended to the farmers of the area and similar locations for obtaining optimum yield but under late sown condition, variety Unnati is preferred to Preeti for obtaining the optimum yield